Pengaruh Return On Assets (ROA), Return On Equity (ROE) Dan Loan To Deposit Ratio (LDR) Terhadap Capital Adequacy Ratio (CAR) Bank BUMN Tahun 2019-2023 - Dimas Pranoto; Atwal Arifin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the impact of Return on Assets (ROA), Return on Equity (ROE), and the Loan to Deposit Ratio (LDR) on the Capital Adequacy Ratio (CAR) in state-owned banks. The method used in this research is panel data regression, with secondary data sourced from the annual reports of state-owned banks from 2019 to 2023. The results of the study show that the best model selected is the Random Effect Model (REM). Based on the data analysis, it was found that ROA, ROE, and LDR variables simultaneously influence CAR. The t-test results indicate that ROA has a significant effect on CAR, while ROE and LDR do not have a significant effect on CAR in state-owned banks. The findings of this study are expected to provide benefits for policymakers as a basis for financial management planning to maintain the bank’s health through CAR, as well as for banking institutions as input for evaluating bank health. Furthermore, these results can also serve as a reference for investors and potential investors in assessing the bank's health before making investments.